Using a Sprayable Biodegradable Polymer to Reduce Soil Evaporation in Greenhouse Conditions - J. Flory; J. Grane; A. Patrignani (Kansas Agricultural Experiment Station Research Reports, 2021)
Sprayable biopolymer membranes (SBM) is an emerging mulching alternative to increase horticultural and agricultural productivity by reducing soil erosion and evaporative losses. The SBM is usually applied in liquid form directly to the soil surface where the polymer molecules form a thin biodegradable film. In order to test this technology, an experiment was performed in greenhouse conditions with the goal of quantifying the impact on soil evaporation rate and biomass accumulation in winter wheat.
Keywords: Soil evaporation; biodegradable polymer; soil water conservation